Microbial translocation across the GI tract - Brenchley, Jason M; Douek, Daniel C (Annual review of immunology, 2012)
The lumen of the gastrointestinal (GI) tract is home to an enormous quantity of different bacterial species, our microbiota, that thrive in an often symbiotic relationship with the host. Given that the healthy host must regulate contact between the microbiota and its immune system to avoid overwhelming systemic immune activation, humans have evolved several mechanisms to attenuate systemic microbial translocation (MT) and its consequences. However, several diseases are associated with the failure of one or more of these mechanisms, with consequent immune activation and deleterious effects on health. Here, we discuss the mechanisms underlying MT, diseases associated with MT, and therapeutic interventions that aim to decrease it.